Andalusia's Mental Image in Modern Omani Literature - Al Ghusaini, Zahir Badar (Dirasat: Human and Social Sciences, 2024)
Objectives: The study's aim is to extrapolate the representation of Andalusia in contemporary Omani writing in order to reveal how Omani writers perceive Andalusia based on factual information and their own mental imagery. Methods: The study employed an inductive and analytical approach, analysing four prose and four poetic examples from contemporary Omani literature to reveal the invocation of Andalusia among Omani writers. Results: The findings confirm the objective representation of Andalusia in contemporary Omani literature, which reflects an emotional value for Omani writers. This perception varies between pride in present-day Spain and feelings of regret over the disappearance of the Arab presence. The Omani cultural appreciation of the value of Andalusia is manifested across various literary genres, including the poetry of Abd al Razzaq Al-Rubaie, Saeed Al-Saqlawi Al-Khalili's muwashshah, "Let’s stop and weep the tears of grief," and the novel Secret of the Morisco. Additionally, within travel literature, works such as Andalusia is a journey between two times and An Eye and a Wing: Travels in the Virgin Islands, Zanzibar, Thailand, Vietnam, Andalusia, and the Empty Quarter. Conclusions: The study emphasizes that Andalusia serves as an objective equivalent in contemporary Omani literature, reflecting a mental perception with emotional value for Omani writers. The collective imagination that absorbs the value of Andalusia in its entirety showcases the Omani writer's appreciation of Andalusian places and characters. The expressive energies infused into the literary texts, featuring characters, demonstrate the Omani writer's awareness of its value, impacting the recipients of the text.